Analisis Volatilitas Variabel Makroekonomi dan Harga Saham Menggunakan Generalized Autoregressive Conditonal Heteroscedasticity (Garch Model) - Paulina Paulina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2022)
Macroeconomic variables often have an impact on stock price volatility and this is needed especially to determine stock price policies in the future. The approach used to see the extent of the volatility of macroeconomic variables on stock prices is the ARCH/GARCH model. This study aims to analyze the nature of stock price volatility in the food and beverage industry in Indonesia using ARCH/GARCH. The data used in this study is secondary data, namely the stock prices of food and beverage industry companies during the period January 2015 to May 2021. The analysis of stock price volatility was carried out with the help of the Eviews 9 software. The results showed the characteristics of the stock price volatility of food and beverage companies based on the ARCH model. /GARCH is quite risky in the short term but not in the long term (indicated by macroeconomic variables of exchange rates, short-term interest rates), so that stock price movements can be anticipated as an early warning system of an increase or decrease in stock prices in the sector. In addition, it can be estimated that the volatility of stock prices in the future is moderate with changes in macroeconomic variables. For policy makers to anticipate changes in macroeconomic variables in certain situations, such as during the current Covid 19 pandemic.